Systematic analysis of SmWD40s, and responding of SmWD40-170 to drought stress by regulation of ABA- and H2O2-induced stomal movement in Salvia miltiorrhiza bunge - Liu, Yuan-Chu (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.